The Importance of Exchange Rate Analysis and the Terrorist Attack of September 11 on the Performance of the International Airborne Transportation sector of Passengers in Brazil - Monçores, Paulo de Jesus; Silva, Wesley Vieira da (Review of Business Management, 2007)
The terrorists’ attacks using commercial aircrafts as mass destruction instruments in North American soil on 09/11/2001 caused great political and social-economic changes all over the world, bringing about a great deal of influence to several Brazilian economic sectors even nowadays. Common sense points out that this event made the crisis faced by airspace Brazilian industry since 1999 even worse, due to exchange dollar rate fluctuations. Through a population average comparison parametric test and using Pearson linear co relational coefficient, this work aims to demonstrate September 11th event and dollar exchange rate real influence over International Travels Expenses Account in Brazilian Balance of Payment and airborne passengers stream to USA before and after the terrorists attacks. The outcomes from statistics data reject null hypothesis of averages equality between international travels expenses and averages equality between boarded passengers to USA, before and after the event, with 95% trust level. By other hand, the Pearson linear co relational coefficient between dollar exchange rate and international travels expenses was 77, 83%, being significant in 5%. Key-words: Airborne transportation sector. Event study. Linear cor relational.